Evaluación nutricional, preferencia alimentaria y anemia en adolescentes del nivel secundaria con residencia estudiantil El Milagro Iquitos, 2023 - Achin Rivas, José Miguel (2023)
The goal of this analysis is to determine the relationship between nutritional evaluation and anemia with respect to food preferences in secondary school adolescents with “El Milagro” Iquitos, 2023 student residence. The research has a quantitative approach, nonexperimental, descriptive, correlational and transversal. This test was carried out by 124 secondary school students, of which 57.3% were male and 42.7% were female.The adolescents were evaluated with anthropometric measurement instruments, where it was detected that 88.7% of men have normal height and in the case of women it is 77.4%, for the indicator they have low height. Women presented more cases with 22.6% and only 11.3% were established in men. It is concluded that no adolescent is tall. Schoolchildren with a normal BMI were entirely boys with 100%; Meanwhile, women obtained a normal BMI with 98.1%, which leads to detecting only one case of overweight in women. In addition, waist measurements were taken, thus demonstrating that both females and males have low PAB, on the men's side it is reflected at 98.6% while in women it is 96.2%, thus presenting a decrease in high PAB in males. only 1.4% and in women 3.8%. Subsequently, they answered a questionnaire on food preferences that consisted of 32 questions, classifying them into ranges of (adequate, regular and deficient) where both female and male sex reach the range of deficient, mostly reflecting regular food preferences with 95.8% in male and female adolescents. 96.2% in female adolescents for the appropriate range, 4.2% are occupied by males and 3.8% by females. At the end of the evaluation, the hemoglobin levels were analyzed through a discard screening, obtaining that the schoolchildren present mild anemia in 22.5% in males and 24.5% in females, it is evident that there is 18.9% that present moderate anemia and It only occurs in the case of women; on the other hand, those who do not have anemia are divided into 77.5% for males and 56.6% for females. Finally we can say that there is a significant relationship between the food preference variables with the body mass index, abdominal perimeter and anemia in the students of the “El Milagro” student residence at the secondary level.